2008
DOI: 10.1007/s12011-008-8260-2
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Copper, Selenium, and Molybdenum Contents in Frequently Consumed Foods and an Estimation of Their Daily Intake in Korean Adults

Abstract: This study aimed to analyze the amounts of copper, selenium, and molybdenum among trace minerals in foods and to evaluate their daily intakes in Korean adults. Contents of copper, selenium, and molybdenum in 366 varieties of foods commonly consumed by Koreans were analyzed using inductively coupled plasma atomic emission spectrometry and inductively coupled plasma mass spectrometry, techniques with low detection limits as well as high reproducibility and precision. Next, we evaluated the status of trace minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
0
12
2
Order By: Relevance
“…Accordingly, Mo intake in these countries is thought to be adequate. The Mo intake of Korean people was estimated to be only 11 mg/day [19]; however, this figure is doubtful because the analytical values adopted in this report were one order of magnitude lower than those of other reports. Since cereals and pulses contain Mo at a very high level, the Mo intake of vegetarians [17] and people who eat a large amount of soybeans [9] is higher than that of the general population.…”
Section: Speciation Of Molybdenum In Foodcontrasting
confidence: 62%
“…Accordingly, Mo intake in these countries is thought to be adequate. The Mo intake of Korean people was estimated to be only 11 mg/day [19]; however, this figure is doubtful because the analytical values adopted in this report were one order of magnitude lower than those of other reports. Since cereals and pulses contain Mo at a very high level, the Mo intake of vegetarians [17] and people who eat a large amount of soybeans [9] is higher than that of the general population.…”
Section: Speciation Of Molybdenum In Foodcontrasting
confidence: 62%
“…Meat products contain energetic minerals that are essential for various biochemical functions in organisms (Bilandzic et al ., 2012; Horita et al , 2011), and low dietary access to mineral elements leads to various human disorders (Melo et al , 2008). In particular, dietary Se, Mg, and K are required for physical functions and these minerals participate in oxidation reduction reactions (Choi et al , 2009). Muscles from two way cross breed of Yorkshire × Large white pigs (Y×LW) had higher Mg, Fe, and Zn contents than those from Large white , and Kanengoni et al (2014) reported that C and P levels were higher in Large white × Landrace pigs than in South African Windsnyer-type indigenous pigs.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted this analysis using ICP-MS because it was suitable for the analysis of low concentrations without large interference (Choi et al 2009). The ICP-MS was operated at 1,400 W forward power with a coolant flow rate of 13.5 l/min, nebulizer gas flow rate of 1.15 l/min with concentric nebulizer.…”
Section: Methodsmentioning
confidence: 99%